2021
DOI: 10.1111/aor.14018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training during hemodialysis in Brazil: A national survey

Abstract: To evaluate the availability and characteristics of exercise training during hemodialysis in Brazil and to identify the reported barriers to exercise program implementation and maintenance. All dialysis units were assessed for eligibility using the database of the Brazilian Society of Nephrology. Each dialysis unit was contacted by telephone and the questions were administered. In dialysis units with exercise training, questions related to personnel involved, exercise components, and program delivery were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The most recent Brazilian dialysis census indicated that an estimated 136,691 individuals were on dialysis in Brazil. Our study found that only 5,360 patients were on IEPs 8 , 11 .Another relevant finding was the biased geographic distribution of the 70 included professionals, who were simply inexistent in nine Brazilian States. The absence of a legal requirement to make physical rehabilitation professionals available in dialysis centers might serve as an explanation for the incredibly low number of such professionals in dialysis centers 12 .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The most recent Brazilian dialysis census indicated that an estimated 136,691 individuals were on dialysis in Brazil. Our study found that only 5,360 patients were on IEPs 8 , 11 .Another relevant finding was the biased geographic distribution of the 70 included professionals, who were simply inexistent in nine Brazilian States. The absence of a legal requirement to make physical rehabilitation professionals available in dialysis centers might serve as an explanation for the incredibly low number of such professionals in dialysis centers 12 .…”
Section: Discussionmentioning
confidence: 57%
“…This cross-sectional study was conducted from April 2019 to June 2020. It was part of a large survey involving dialysis centers in Brazil 8 . Consent from study participants was given over the phone or via the electronic form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of exercise professionals within the dialysis staff may ensure effective and sustainable intradialytic exercise programmes as a clinical routine (Barros, et al, 2021; Bennett et al, 2010). A recent survey study performed in Brazil showed that only 16% of the dialysis centres had an intradialytic exercise programme integrated into the clinical routine (Barros et al, 2021). The most commonly reported barriers to the implementation were a lack of budgetary and experienced human resources along with a void in standardized clinical protocols or guidelines in the field.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adherence of patients to intradialytic exercise programmes is strongly associated with the presence of exercise professionals, and patients are twice as likely to exercise if an exercise professional is present (Parker et al, 2021). The presence of exercise professionals within the dialysis staff may ensure effective and sustainable intradialytic exercise programmes as a clinical routine (Barros, et al, 2021;Bennett et al, 2010). A recent survey study performed in Brazil showed that only 16% of the dialysis centres had an intradialytic exercise programme integrated into the clinical routine (Barros et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%